A simple spectrophotometric method for the determination of methyldopa using p-chloranil in the presence of Hydrogen Peroxide - Gotardo, Mara Andréia; Lima, Liliane Spazzapam; Sequinel, Rodrigo; Rufino, José Luiz; Pezza, Leonardo; Pezza, Helena Redigolo (Eclética Química, 2008)
A simple, rapid and sensitive spectrophotometric method has been developed for the determination of methyldopa in pharmaceutical formulations. The method is based on the reaction between tetrachloro-p-benzoquinone (p-chloranil) and methyldopa, accelerated by hydrogen peroxide (H2O2), producing a violet-red compound (λmax = 535 nm) at ambient temperature (25.0 ± 0.2 0C). Experimental design methodologies were used to optimize the measurement conditions. Beer’s law is obeyed in a concentration range from 2.10 x 10-4 to 2.48 x 10-3 mol L-1 (r = 0.9997). The limit of detection was 7.55 x 10-6 mol L-1 and the limit of quantification was 2.52 x 10-5 mol L-1. The intraday precision and interday precision were studied for 10 replicate analyses of 1.59 x 10-3 mol L-1 methyldopa solution and the respective coefficients of variation were 0.7 and 1.1 %. The proposed method was successfully applied to the determination of methyldopa in commercial brands of pharmaceuticals. No interferences were observed from the common excipients in the formulations. The results obtained by the proposed method were favorably compared with those given by the Brazilian Pharmacopoeia procedure at 95 % confidence level.